Is NGO aid not so different after all? Comparing the allocation of Swiss aid by private and official donors - Peter Nunnenkamp; Janina Weingarth; Johannes Weisser (Kiel Institute for the World Economy (IfW), 2008)
Being closer to the poor, NGOs are widely believed to provide better targeted aid than state agencies. But empirical evidence is largely lacking. We contribute to closing this gap by drawing on an exceptionally detailed Swiss database that covers different forms of NGO aid and several official aid benchmarks. The differentiated Tobit estimations account for both altruistic and selfish aid motivations. It turns out that it depends on the source of NGO funding as well as the choice of the official benchmark whether or not NGOs provide better targeted aid. In contrast to widespread belief, however, the allocation of self-financed NGO aid reveals striking similarities to the allocation of official Swiss development aid.
Keywords: F35; 330; NGO aid; Official aid; Aid allocation; Tobit models; Entwicklungshilfe; Vergleich; Private Entwicklungshilfe; Nichtregierungsorganisation; Tobit-Modell; Schätzung; Schweiz